2017
DOI: 10.1139/cjm-2016-0519
|View full text |Cite
|
Sign up to set email alerts
|

Entry, infection, replication, and egress of human polyomaviruses: an update

Abstract: Polyomaviruses (PyVs), belonging to the family Polyomaviridae, are a group of small, nonenveloped, double-stranded, circular DNA viruses widely distributed in the vertebrates. PyVs cause no apparent disease in adult laboratory mice but cause a wide variety of tumors when artificially inoculated into neonates or semipermissive animals. A few human PyVs, such as BK, JC, and Merkel cell PyVs, have been unequivocally linked to pathogenesis under conditions of immunosuppression. Infection is thought to occur early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 196 publications
(237 reference statements)
0
20
0
Order By: Relevance
“…BKPyV and JCPyV were discovered in 1971. In the last 15 years, mainly due to the development of new high-throughput sequencing techniques, other twelve HPyVs have been discovered (MCPyV, KIPyV, WUPyV, TSPyV, HPyV6, HPyV7, HPyV9, HPyV10, HPyV12, STLPyV, NJPyV and LIPyV) [2,3]. HPyV infection usually occurs early in life through a fecal-oral transmission mechanism and persists for the lifetime of the infected subject.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…BKPyV and JCPyV were discovered in 1971. In the last 15 years, mainly due to the development of new high-throughput sequencing techniques, other twelve HPyVs have been discovered (MCPyV, KIPyV, WUPyV, TSPyV, HPyV6, HPyV7, HPyV9, HPyV10, HPyV12, STLPyV, NJPyV and LIPyV) [2,3]. HPyV infection usually occurs early in life through a fecal-oral transmission mechanism and persists for the lifetime of the infected subject.…”
Section: Introductionmentioning
confidence: 99%
“…HPyV infection usually occurs early in life through a fecal-oral transmission mechanism and persists for the lifetime of the infected subject. In natural hosts, these viruses establish a productive infection, although in heterologous non-permissive hosts, the virus establishes latency with potential integration into the host genome [2]. HPyVs are very ubiquitous in nature and their association with some pathologies, cancer in particular, is under intensive investigation [4].…”
Section: Introductionmentioning
confidence: 99%
“…The life cycle of a virus begins with the entry of the host cell. Replication of viral genomes, synthesis of viral proteins, assembly of viral particles, and release of viruses from host cells depend largely on host mechanisms (1, 2). It is reported that the stability of viral mrna is regulated by the dcp1-dcp2 complex located in the P-body (the processing bodies) (3, 4).…”
Section: Introductionmentioning
confidence: 99%
“…Polyomaviruses are double stranded DNA, nonenveloped viruses that undergo genome replication and viral assembly in the nucleus. Most polyomaviruses, excluding JC virus (JCPyV), enter the cell via receptor binding at caveolae (151). JCPyV enters cells via clathrin-mediated endocytosis (151).…”
Section: Polyomavirusesmentioning
confidence: 99%
“…Most polyomaviruses, excluding JC virus (JCPyV), enter the cell via receptor binding at caveolae (151). JCPyV enters cells via clathrin-mediated endocytosis (151). Resulting caveosomes are trafficked to the ER using the microtubule network, where the viral capsid becomes inserted into the ER lumen (151).…”
Section: Polyomavirusesmentioning
confidence: 99%